Pollach, Edith (audio interview #1 of 4) - Pollach, Edith (3/2/1921 - 11/30/2007); Pfister, Janet, interviewer
INTERVIEW DESCRIPTION - This is the first of four interviews with Edith Pollach. The interview consists of three tapes. It was conducted by a friend of Pollach's. The audio quality of the interview is good. 2/9/1999